Love: an approach to texts - Lorsung, Éireann (2013)
This dissertation responds to the question, "What would it be like, what would it mean, to approach texts lovingly?" in terms of the work of 20th-century theorists, writers, and thinkers such as Jacques Derrida, Roland Barthes, Luce Irigaray, Helene Cixous, Gilles Deleuze and Felix Guattari, Brian Massumi, Jean-Luc Marion, E. E. Cummings, Rainer Maria Rilke, Teresa Brennan, and W. J. T. Mitchell. In order to demonstrate the appropriateness and place of love in the philosophical canon, the dissertation combines a consideration of affect with these writers' work. Beginning with an exemplary reading of Cy Twombly's painting The Ceiling, the then dissertation adapts Mitchell's question "What do pictures want" to an approach to texts, as defined with reference to Barthes. An introduction and literature review trace the places love in texts by Plato, Freud, Lacan, Cixous, and a host of writers who fall under the rubric of 'affect theorists'. Because an approach to texts is the dissertation's focus, a chapter is spent discussing the possibilities for deconstruction to be part of such an approach. Derrida's work is constellated with that of Cixous, Irigaray, Marion, and Brennan in order to emphasise the integrity of sensory and affective information to such an approach. The writing of Rilke and Cummings provides examples of an authorial approach to texts that can inform a readerly one, and serves to further expand the canon of texts that suggest the possibility of this approach. The final chapter is a second exemplary reading of the story of Moses and the burning bush. Deliberately aiming to stretch the expectations of scholarly work, I combine the anecdotal, the affective, and the textual as modes of engaging with and ways of knowing about love.